If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-4x + 5) + 8 = -2(2x + 6) + -10 Reorder the terms: 3(5 + -4x) + 8 = -2(2x + 6) + -10 (5 * 3 + -4x * 3) + 8 = -2(2x + 6) + -10 (15 + -12x) + 8 = -2(2x + 6) + -10 Reorder the terms: 15 + 8 + -12x = -2(2x + 6) + -10 Combine like terms: 15 + 8 = 23 23 + -12x = -2(2x + 6) + -10 Reorder the terms: 23 + -12x = -2(6 + 2x) + -10 23 + -12x = (6 * -2 + 2x * -2) + -10 23 + -12x = (-12 + -4x) + -10 Reorder the terms: 23 + -12x = -12 + -10 + -4x Combine like terms: -12 + -10 = -22 23 + -12x = -22 + -4x Solving 23 + -12x = -22 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 23 + -12x + 4x = -22 + -4x + 4x Combine like terms: -12x + 4x = -8x 23 + -8x = -22 + -4x + 4x Combine like terms: -4x + 4x = 0 23 + -8x = -22 + 0 23 + -8x = -22 Add '-23' to each side of the equation. 23 + -23 + -8x = -22 + -23 Combine like terms: 23 + -23 = 0 0 + -8x = -22 + -23 -8x = -22 + -23 Combine like terms: -22 + -23 = -45 -8x = -45 Divide each side by '-8'. x = 5.625 Simplifying x = 5.625
| x^2+8-45=0 | | -6.9y=-55.2 | | 6(x-9)=5(2+x) | | -5x+3(2x-4)=7x-2(5x-4)+12 | | 7x=4x+27 | | 2x-5/3=x | | 223600-17740x=1969900 | | 12x+9=10x+3 | | 9p^2+73n+70=0 | | 3x+6=-27 | | 9-2x(x+4)-10(25-x+4)=5-3x-4(x+1) | | 100-4x=41x+15 | | 20=-4t | | 7-9x=62-44x | | 2t+4=16 | | 28u^48-22u^8vy^7= | | 2236000-17740x=2324700 | | 6x^2=6x | | x+1=39 | | 24-(x+3)=12+2(9-2x) | | 4x-5=11-82 | | -x-2y=-3 | | 30=-6t | | 3=-6t | | x^3-3x^2+6x-12=0 | | (2x+4)(4x+6)(6x+8x)=0 | | 2/3a=12-4 | | 49=-x | | x^5=1.25 | | 4x^2+23x+15x=0 | | 3m/2-2/4=9/2-m | | -4b^2+36=0 |